Ultrasound Contrast Agents For Ultrasound Molecular Imaging - Tranquart, F.; Arditi, M.; Bettinger, T.; Frinking, P.; Hyvelin, J. M.; Nunn, A.; Pochon, S.; Tardy, I. (Zeitschrift für Gastroenterologie, 2014)
Ultrasound is a real-time imaging technique which is widely used in many clinical applications for its capacity to provide anatomic information with high spatial and temporal resolution. The advent of ultrasound contrast agents in combination with contrast-specific imaging modes has given access to perfusion assessments at an organ level, leading to an improved diagnostic accuracy. More recently, the development of biologically-targeted ultrasound contrast agents has expanded the role of ultrasound even further into molecular imaging applications. Ultrasound molecular imaging can be used to visualize the expression of intravascular markers, and to assess their local presence over time and/or during therapeutic treatment. Major applications are in the field of inflammation and neoangiogenesis due to the strictly intravascular presence of microbubbles. Various technologies have been investigated for attaching the targeting moiety to the shell from simple biotin-avidin constructs to more elaborated insertion within the shell through attachment to PEG residues. This important improvement has allowed a clinical translation of initial pre-clinical investigations, opening the way for an early detection and an accurate characterization of lesions in patients. The combination of anatomic, functional and molecular information/data provided by contrast ultrasound is a powerful tool which is still in its infancy due to the lack of agents suitable for clinical use. The advantages of ultrasound techniques combined with the molecular signature of lesions will represent a significant advance in imaging in the field of personalized medicine.
Keywords: Mikrobläschen; kontrastverstärkterUltraschall; molekulare Bildgebung; VEGFR2; Selektine; gastrointestinaler Stromatumor (GIST); kolorektales Karzinom; gastro-entero-pankreatische Tumoren